Electrochemical Behavior of Polycrystalline Copper in Aqueous Phosphate Buffered Solution During CO2 Reduction. - Salimon, Jumat; Kalaji, Maher (Universiti Putra Malaysia Press, 2003)
The redox processes occurring on the copper surface in phosphate buffered solution were investigated. The results show that the oxidation and the reduction of copper surface occur in a slow process with hydrogen evolution region proceeding at potential more negative than -1.0 V. It is found that the hydrogen evolution region was not affected by the anodic potential limits. The anodic film forms on the copper surface are reduced possibly in quasireversible manner. In CO2-saturated solution, the loss of copper to the solution increases due to the formation of copper soluble species. This process is further enhanced with the polarization process, where copper(I)-carbonyl forms to the bulk solution. The results also show that the electrochemical behavior of copper electrode is dramatically changed by the polarization process. The hydrogen evolution region is greatly depressed due to the CO2 reduction process. Consequently, the reduction of CO2 is not pronounced on the copper surface except for the electrode surface has which been polarized at high cathodic potential for a period of time.